CYBERBULLYING DI KALANGAN REMAJA PADA PERKEMBANGAN TEKNOLOGI ABAD 21 - Rahmi, Silatul; Oruh, Shermina; Agustang, Andi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Cyberbullying is a new form of bullying behavior that is rampant among adolescents along with the development of digital technology. The purpose of this research is to examine the phenomenon of cyberbullying among adolescents through a literature study. The research method uses a literature review by analyzing various journals and literature related to the topic of cyberbullying. The results of the study show that cyberbullying has unique characteristics such as the anonymity of perpetrators and victims which is much wider than traditional bullying. Some of the main factors causing the rise of cyberbullying include the anonymity of the perpetrators, low digital literacy, weak regulation of social media, and psychological factors of adolescents. The impact is quite serious for victims, ranging from depression, dropping out of school, to suicide. Efforts to prevent and handle cyberbullying need to be carried out comprehensively by involving the roles of parents, schools, government, and adolescents themselves. Further research is needed to find effective solutions in dealing with the problem of cyberbullying so that the risks to adolescents can be minimized.